How Computer.Mediated Communicatlon (CMC) Can Work to Enhance Dlstonoe Delivery of Courses. - Cheryl L. Bielema (Journal of Applied Communications, 1997)
An innovation, such as requiring connectivity and E-mail in a graduate course, can create barriers for the new users. The purpose of this study was to-better understand one such innovation: the use of computer-mediated instructional techniques for a distance-learning environment. The participants were instructors and extramural students in two audio graphics courses. E-mail was archived, coded, and sorted to show differences in use among the students, while interviews were conducted with selected students to reveal any barriers and benefits they experienced. The findings suggest improvements are needed in facilitating electronic discussions: structuring learning projects, specifically, self-directed learning contracts; and better planning for different learning styles.